(untitled) (Applied Biological Research, 2017)
In Kashmir, a large number of 1-day old chicks are procured from neighbouring states which puts birds to early life stress during transportation and affects their growth performance. The present study was aimed to evaluate the role of different durations of post-hatch delay in feeding in Chabro chicken. Four hundred 1-day old Chabro chicks were randomly divided into 5 groups with 4 replicates of 20 birds each and subjected to different durations of delay in post-hatch delay feeding for 6 weeks. Control chicks were offered feed at hatchery while in other groups feeding was started after delay of 12, 24, 48 and 72 h. As the post-hatch feeding was delayed at the start of experiment, it caused a significant (P<0.05) decrease in chick body weight with lower weight observed in groups subjected to 24, 48 and 72 h delay in feeding as compared to control. Thereafter, the body weights decreased steadily with increase in post-hatch delayed feeding with highest decrease in group subjected to 72 h feeding delay. The average weekly feed consumption showed a steady increasing trend with increase in post-hatch feeding delay. FCR of birds worsened with increase in post-hatch feeding delay. There was no significant change in various blood biochemical parameters, except for SGPT. Higher feed cost per kg live weight gain was observed in groups subjected to longer durations of delay in feeding. To circumvent negative effects of delayed feeding, early feeding strategies need may be adopted which include proper hatchery feeding and feeding during transportation of birds.